Developing Moderate Islamic Education: Special Reference to Al-Daghasyi’s Thought and Its Contextualization in Indonesia - Sabarudin Sabarudin; Mahmud Arif; Zainudin Zainudin; Akhyak Akhyak; Mirna Guswenti; Rafidah Abdullah (International Journal of Educational Narratives, 2025)
Background. One of the main agendas for promoting a harmonious life in a diverse society strengthening religious moderation, which has become a priority program of the government. Purpose. This study tries to contribute to the reinforcement of religious moderation through literary explorations concerning the concept of moderate Islamic education. Method. This research was a study of al-Daghasyi’s educational thoughts through literary explorations which were then positioned as a dialogue partner to formulate the significant concept for the development of moderate Islamic education. Results. According to al-Daghasyi, when education is based on moderate Islam, it will play an important role in preventing deviant attitudes and behaviours, such as intolerance and extremism, namely al-ifr?th and al-tafrîth (liberalism and radicalism). Conclusion. This study has significant implications for instructional practices in The real endeavor does not involve weapon confrontations but fundamentally deals with preventing warfare and injustice.